2020
DOI: 10.3390/ijerph17041361
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for Mass Gatherings: Factors to Consider According to the Rescue Authorities

Abstract: Background: Mass gatherings cause a need for multi-authority preparedness in order to ensure the safety of the event participants and to minimize delays in response for emergencies. Rescue authorities are key players in the pre-planning phase; however, their own point of view regarding all aspects of preparedness for mass gatherings is not well known. The aim of this study was to investigate what factors, according to the rescue authorities, need to be considered when preparing for mass gatherings. Method: Sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
(98 reference statements)
3
14
0
Order By: Relevance
“…Our results confirm previous findings that showed that most missions during MG events are allocated to EMS, whereas the increase in the rescue service workload is minor [ 1 , 6 ]. Furthermore, previous studies support the finding that MG events impact local healthcare resources [ 2 , 3 , 31 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results confirm previous findings that showed that most missions during MG events are allocated to EMS, whereas the increase in the rescue service workload is minor [ 1 , 6 ]. Furthermore, previous studies support the finding that MG events impact local healthcare resources [ 2 , 3 , 31 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…As resources in smaller settlements may be more easily overwhelmed than in bigger cities, event organizers’ own levels of preparedness need special focus and attention. This conclusion is supported by previous studies indicating that austere environments also create a need for stronger preparedness for event organizers [ 6 , 30 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations